2021
DOI: 10.1002/cjp2.218
|View full text |Cite
|
Sign up to set email alerts
|

High tumor cell platelet‐derived growth factor receptor beta expression is associated with shorter survival in malignant pleural epithelioid mesothelioma

Abstract: Malignant pleural mesothelioma (MPM) has a rich stromal component containing mesenchymal fibroblasts. However, the properties and interplay of MPM tumor cells and their surrounding stromal fibroblasts are poorly characterized. Our objective was to spatially profile known mesenchymal markers in both tumor cells and associated fibroblasts and correlate their expression with patient survival. The primary study cohort consisted of 74 MPM patients, including 16 patients who survived at least 60 months. We analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
2
4
0
Order By: Relevance
“…SPARC expression in tumor-associated stroma is instrumental in tumor survival and progression and serves as a prognostic factor 14,15,17 . In mesothelioma, SPARC is linked to epithelial-mesenchymal transition, 18 and both its expression in tumor stromal cells and blood SPARC levels correlate with prognosis 19,20 . In the current study, SPARC was found to be positive in mesothelioma cells and negative in lung cancer cells.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…SPARC expression in tumor-associated stroma is instrumental in tumor survival and progression and serves as a prognostic factor 14,15,17 . In mesothelioma, SPARC is linked to epithelial-mesenchymal transition, 18 and both its expression in tumor stromal cells and blood SPARC levels correlate with prognosis 19,20 . In the current study, SPARC was found to be positive in mesothelioma cells and negative in lung cancer cells.…”
Section: Discussionsupporting
confidence: 52%
“…14,15,17 In mesothelioma, SPARC is linked to epithelial-mesenchymal transition, 18 and both its expression in tumor stromal cells and blood SPARC levels correlate with prognosis. 19,20 In the current study, SPARC was found to be positive in mesothelioma cells and negative in lung cancer cells. In the stromal context, focal-to-diffuse SPARC expression was observed in endothelial cells, fibroblasts, and macrophages.…”
Section: Discussionsupporting
confidence: 51%
“…We found that the genes encoding PDGFRB, CSPG4, and COL1A2, which are highly expressed in MPM and correlate with MPM patient prognosis as reported earlier, were almost exclusively expressed in cluster 3 (Figure 3d). 28–30 All cluster 4 patients and 55% of cluster 3 patients belonged to the epithelioid pathology type, but showed significant differences in survival time. Therefore, we explored the differences between cluster 3 and cluster 4 only in epithelial‐type patients and found that they exhibited similar overall characteristics, which indicated that the difference in pathological type was not so important after classification according to alternative splicing clusters.…”
Section: Resultsmentioning
confidence: 99%
“…The clinical characteristics of the study population and specific details regarding the tissue microarrays have been described ( 20 ). We excluded patients with biphasic histology (n = 5).…”
Section: Methodsmentioning
confidence: 99%
“…The mfIHC staining, scanning, and digital cell–based image analysis methods have been previously described ( 20 , 21 ) and were utilized in the current study as described previously. Briefly, we designed and optimized five mfIHC panels (shown in Supplementary Table S1 ) including 21 antibodies targeting immune cell–specific antigens and analyzed the immune cell populations of interest ( Table 1 ) from the multichannel images using cell-based image analysis method.…”
Section: Methodsmentioning
confidence: 99%